Effects of splenectomy on serum lipids and experimental atherosclerosis - Asai, K; Kuzuya, M; Naito, M; Funaki, C; Kuzuya, F (Angiology, 1988)
The authors examined the effects of splenectomy on serum lipids in patients with hematologic disease, in rabbits, and also in cholesterol-fed rabbits with experimental atherosclerosis. Serum cholesterol was determined in patients with hypersplenism before and after splenectomy. Meanwhile serum lipids were determined in two groups of rabbits: splenectomy group (Spx group, n = 19), and sham operation group (Sham group, n = 14) before and after the operation. Then the rabbits were divided into four subgroups: cholesterol-fed groups--Spx-C (n = 12) and Sham-C (n = (9), and normal-chow-fed groups--Spx-N (n = 7) and Sham-N (n = 5). The Spx-C and the Sham-C rabbits were fed 1% cholesterol diet and the Spx-N and Sham-N rabbits were fed normal chow for twelve weeks. In patients preoperative serum cholesterol levels were low, and significant increase in serum cholesterol was observed following splenectomy. In rabbits, the Spx-C group showed significantly higher levels of serum cholesterol, triglycerides, and phospholipids in contrast to lower levels of high density lipoprotein cholesterol, as compared with the Sham-C group. The percentage of aortic plaque area in the Spx-C group tended to be higher than that in the Sham-C group. On the other hand, the Spx-N and the Sham-N group showed no difference in serum lipids during twelve weeks. The worsening of atherosclerosis in the Spx-C group was considered to be mainly due to an enhanced hyperlipidemia. Their results suggest a possible role of the spleen in lipid metabolism, in particular the existence of a splenic factor that can cause hypocholesterolemia in hyperplenism and can suppress hyperlipidemia.